2021
DOI: 10.3390/jmse9060620
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nanosilica for Increasing Dune Erosion Resistance during a Sea Storm

Abstract: Dune recovery interventions that integrate natural, sustainable, and soft solutions have become increasingly popular in coastal communities. In the present study, the reliability of an innovative non-toxic colloidal silica-based solution for coastal sand dunes has been verified for the first time by means of laboratory experiments. An extensive experimental campaign aimed at studying the effectiveness of the use of nanosilica has been conducted in the 2D wave flume of the EUMER laboratory at the University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In a previous study of catenarybead dunes, Zheng et al ( 2016) suggested that typhoons (e.g., Fenghuang, 23 September 2014) may have influenced the development of the catenary-bead dunes, as typhoons can cause severe hydrodynamic changes [20]. The above views were also supported by Felice et al ( 2022) [29] Based on this, the catenary-bead dunes may be considered instantaneous bed forms after the typhoon. Campmans et al (2017) have also confirmed that storms influence dune morphodynamics [30].…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study of catenarybead dunes, Zheng et al ( 2016) suggested that typhoons (e.g., Fenghuang, 23 September 2014) may have influenced the development of the catenary-bead dunes, as typhoons can cause severe hydrodynamic changes [20]. The above views were also supported by Felice et al ( 2022) [29] Based on this, the catenary-bead dunes may be considered instantaneous bed forms after the typhoon. Campmans et al (2017) have also confirmed that storms influence dune morphodynamics [30].…”
Section: Discussionmentioning
confidence: 86%
“…The sixth published paper is entitled "Use of Nanosilica for Increasing Dune Erosion Resistance during a Sea Storm" by Leone et al [6]. In this study, the reliability of an innovative non-toxic colloidal silica-based solution for coastal sand dunes was verified for the first time using laboratory experiments.…”
mentioning
confidence: 79%
“…In certain cases, dike maintenance and (sur)elevation can have an enormous impact on historical structures, landscape, mobility networks and accessibility to the sea, particularly in those areas that heavily rely on tourism. For that, many recent research projects focused on the development of techniques inspired and supported by nature (the so-called naturebase solutions NBS), used to tackle societal challenges such as the mitigation of CO 2 emissions, protection from pluvial and fluvial floods, as well as coastal floods associated with sea level rise, providing both benefits to humans and to the natural environment [7][8][9][10][11]. The expansion and restoration of sand dunes, creation of wetlands, organic material groynes and reefs to support flora and fauna repopulation are sustained by a wide range of professional figures and supported by public international institutions.…”
Section: Introductionmentioning
confidence: 99%